Surgical Excision of Orbital Progressive Granular Cell Tumour - Demetrio Germanò; Hossein Mostafa Elbadawy; Diego Ponzin; Daniele Ferro; Leonardo Priore (Case Reports in Ophthalmological Medicine)
Granular cell tumour (GCT) is mostly benign lesion first described by Abrikossoff and named after him. Most cases are reported in the head and neck area, where the tongue is the most common site. Here we review previous cases in the literature for GCT in the orbit and present a new case. A 49-year-old male presented with apparent exophthalmos. Examination of the patient revealed the presence of a mass in the bottom side of the orbit. A substantial progress was noted after two months from the initial examination using computed tomography (CT) scan. An orbital mass was extracted and histological analysis showed signs typical for GCT. Immunohistochemistry was positive for S-100; the biopsy showed no mitotic or necrotic areas. Proptosis was resolved after surgery and a six-year follow-up CT scan was performed. We conclude that rapid progress of the tumour does not necessarily suggest malignancy.